Primary leiomyosarcoma of the fallopian tube: A case report and literature review. Issue 17 (April 2018) - You, Di; Wang, Qilin; Jiang, Wei; Lin, Lin; Yi, Tianjin; Zhao, Lingjun; Li, Maomao; Wang, Ping
Abstract: Rationale: Primary leiomyosarcoma (LMS) of the fallopian tube is extremely uncommon. To the best of our knowledge, so far only 21 cases of primary fallopian tube LMS have been reported in English-language literature. No new case has been reported in the past 7 years. Patient concerns: A 44-year-old premenopausal patient presented with a 5-day history of lower abdominal pain. Diagnoses: Pelvic ultrasonography detected an 8.8 × 7.8 × 6.5 cm solid and cystic mass in the left side of the pelvic cavity. The tumor was diagnosed as a primary fallopian tube LMS on paraffin section. Interventions: The patient treated surgically followed by 4 cycles of postoperative chemotherapy with dacarbazine and DDP. Outcomes: The patient succumbed to the disease 27 months after the initial therapy. Lessons: Tube LMS is a rare malignant tumor with unknown etiology, difficult early diagnosis, highly invasiveness, high local recurrence and distant metastasis rate, rapid progress, and poor prognosis. It is extremely rare so we can only summarize limited experience from limited data. Every case of tubal LMS is worth being reported.